2020
DOI: 10.1017/s0950268820000850
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for HIV prevention and control among men who have sex with men in China

Abstract: In recent years, men who have sex with men (MSM) constitute a major group of HIV transmission in China. High primary drug-resistance (PDR) rate in MSM also represents a serious challenge for the Chinese antiretroviral therapy (ART) program. To assess the efficiency of ART in controlling HIV/AIDS infection among MSM, we developed a compartmental model for the annually reported HIV/AIDS MSM from 2007 to 2019 in the Zhejiang Province of China. R 0 was 2.3946 (95% CI (2.2961-2.4881)). We predict that 90% of diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The data in this article come from Mukandivire et al, 2010, Lu et al, 2020, and other assumed/ estimated data.…”
Section: Data Availabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The data in this article come from Mukandivire et al, 2010, Lu et al, 2020, and other assumed/ estimated data.…”
Section: Data Availabilitymentioning
confidence: 99%
“…Various improvements have been made to May and Anderson's early models, [23][24][25] and particular issues have been discussed by researchers. 12, In Lu et al 2020 27 fostered a compartmental model for the yearly revealed HIV/AIDS MSM in the Zhejiang Region of China between 2007 to 2019 and anticipated that 90 percent of people tested for HIV/AIDS will have received treatment by 2020, while the screened extent will remain as low as 40 percent, and that antiretroviral treatment (ART) can actually control the transmission of HIV, even within the sight of medication opposition. In Rana and Sharma, 2020 30 presented a simple Likely to be exposed-Infected (i.e.SI) form of HIV/AIDS mathematical model, in view of the supposition that changing from an AIDS-infected to an HIV-infected individual is conceivable, in order to understand disease dynamics and develop strategies to reduce or control disease transmission among individual.…”
Section: Introductionmentioning
confidence: 99%
“…Various improvements have been made to May and Anderson's early models, [23][24][25] and particular issues have been discussed by researchers. 12, In Lu et al 2020 27 fostered a compartmental model for the yearly revealed HIV/AIDS MSM in the Zhejiang Region of China between 2007 to 2019 and anticipated that 90 percent of people tested for HIV/AIDS will have received treatment by 2020 neglecting those that fall out of treatment, while the screened extent will remain as low as 40 percent, and that antiretroviral treatment (ART) can control the transmission of HIV, even within the sight of medication opposition. Rana and Sharma, 2020 30 presented a simple Likely to be exposed-Infected (i.e.SI) form of the HIV/AIDS mathematical model, given the supposition that changing from an AIDS-infected to an HIV-infected individual is conceivable, to understand disease dynamics and develop strategies to reduce or control disease transmission among individual.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increase in the number of studies on HIV/AIDS transmission [12][13][14][15][16][17][18][19][20][21][22]. For example, Moya and Marrero [12] presented a stochastic model using Markov chains to study the transmission of HIV/AIDS and control chain elements proposed control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Ogunlaran and Noutchie [18] proposed a mathematical model with two control variables, where the uninfected CD4+T cells follow the logistic growth function and the incidence term is saturated with free virus and apply optimal control approach to maximize the concentration of uninfected CD4+T cells in the body by using minimum drug therapies. Lu et al [19] developed a compartmentalized model for annual reporting of HIV in men who have sex with men (MSM) from 2007 to 2019 in the Zhejiang region and proved that the 90-90-90 target alone may not eliminate the HIV epidemic in Chinese men who have sex with men.…”
Section: Introductionmentioning
confidence: 99%